Self-care in nursing: A bibliometric analysis (1976–2023) - Mahsa Hosseini; Soheila Shamsikhani; Masoomeh Noruzi Zamengani; Sediqullah Ahmadi; Ali Jadidi (International Journal of Africa Nursing Sciences)
Context: This study conducted a science mapping analysis of Self-care for nurses research until 1 January 2024. Self-care is a crucial element in promoting global health. Self-care can lead to the health and happiness of nurses. The purpose of this study was to identify the authoritative journals in this field, and topics related to nurses’ self-care. Evidence Acquisition: The present study was a bibliometric analysis that used science mapping techniques and data was extracted from the Web of Science and Scopus. Based on the study population and the outcome, Self-care and nurses were considered as the main search terms. Data collection and analysis may be divided into two main: descriptive and bibliometric. The use of VOSviewer for analysis. Results: This study retrieved 102 publications which, 74 (58%) were articles and 12 (11%) were reviewed articles. The United States is the most effective country in this field with the most publications and citations. Common related to self-care, nursing, work factors, and health-related. The International Journal of Nursing Studies from Elsevier has the most citations in the WOS and Scopus databases. Conclusions: Due to the lack of research in the field, there is a concern to produce information and research in this field. The importance of research in this field is related to the role of nurses in the health system. self-care can help improve global health by improving the physical and mental health of nurses. Therefore, it is suggested that pay special attention to Self-care for nurses.